Marcadores moleculares envolvidos no metabolismo do folato em pacientes com câncer de mama - Gimenez-Martins, Ana Paula D'alarme (2015)
Introduction: Breast cancer is the second most common cancer in the world, being the most common among women. This disease is multifactorial involving lifestyle, hormonal, environmental and genetic factors. The folate metabolism may be associated with the development of breast cancer, since folate plays a crucial role in the synthesis, regulation and DNA methylation. Polymorphisms in genes involved in metabolism, such as MTHFR C677T, MTHFR A1298C, MTR A2756G and MTRR A66G modify the efficiency of the enzymes, causing abnormal changes in gene expression, inactivation of tumor suppressor genes and activation of oncogenesis. Objectives: To investigate the frequency of polymorphisms in MTHFR C677T (rs1801133), MTHFR A1298C (rs1801131), MTR A2756G (rs1805087) and MTRR A66G (rs1801394) genes in patients with breast cancer comparing to individuals with no history neoplasia; to evaluate the association between polymorphisms and risk factors (age, smoking habits, alcohol consumption, number gestations, body mass index and hormone therapy) and the clinical histopathological parameters (tumor size, node involvement, metastasis and cancer subtypes) of breast cancer. Materials and methods: The present case-control study involved 606 Brazilian women, 128 case group and 478 control group. For molecular analysis, genomic DNA was extracted from peripheral blood leukocytes. Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) was used in the genotyping of polymorphisms in the genes MTHFR and MTR and PCR real time for polymorphsm in gene MTRR. The clinical and pathological data were obtained from medical records. For statistical analysis, program used were MINITAB 14.0 (multiple logistic regression), and SNPstats (inheritance models and Hardy-Weinberg Equilibrium) program. Results: Women aged 50 and over (OR: 2.65; 95% IC: 1.65-4.26; p<0.001) and alcohol consumption (OR: 1.76; 95% IC: 1.09-2.85; p=0.021) are associated increased risk for breast cancer. Smoking habits (OR:1.07; 95%CI:0.65-1.79; p=0.782), number of pregnancies (OR:0.86; 95%CI:0.54- 1.38; p=0.536), BMI ≥25 Kg/m2 (OR:1.24; 95%CI:0.75-2.06; p=0.405), and hormone therapy (OR: 1.41; 95%CI:0.86-2.33; p=0.174) are not associated with the risk of breast cancer. For MTHFR A1298C (rs1801131), we observed reduced risk of developing disease in codominant model (genotype CC – OR: 0.22; 95%CI: 0.06-0.74; p=0.014), recessive model (OR: 0.22; 95%CI: 0.07- 0.76; p=0.004), and log-additive model (OR: 0.70; 95%CI: 0.49-0.98; p=0.035), however no significant associations was found between MTHFR C677T (rs1801133), MTR A2756G (rs1805087), and MTRR A66G (rs1801394) polymorphisms and breast cancer risk. In relation to clinical histopathological parameters, we not found significant association between polymorphisms studies and breast tumors. Conclusions: Women aged 50 and over and who drink alcohol have a higher risk of developing breast cancer. The MTHFR A1298C polymorphism was associated with decreased risk in breast cancer. This is the first study the association between the genotypic these polymorphisms, and clinical histopathological parameters involving women population from the Northwest region of Sao Paulo State, Brazil.